Long series of Swiss seasonal precipitation: regionalization, trends and influence of large‐scale flow. (23rd December 2015) - Scherrer, Simon C.; Begert, Michael; Croci‐Maspoli, Mischa; Appenzeller, Christof
ABSTRACT: Quantifying precipitation variability and trends is difficult and merits regular reassessment. In the present study, the seasonal homogenized precipitation series in Switzerland is investigated for the period 1901–2013 in terms of trends, inter‐annual variability and the influence of large‐scale flow. An objective clustering is applied, resulting in 32 distinct precipitation regions. Trends are analysed for all 32 regions with moving trend windows, and statistical significance ( p < 0.05) is assessed with Theil–Sen trend estimates and nonparametric Mann–Kendall trend tests. Inter‐annual precipitation varies considerably regionally and seasonally. Of 2720 analysed trend windows of 33–113 years in length, 194 (7.1%) show a significantly positive trend and 10 (0.4%) a significantly negative trend. Most of the significantly positive trends are found for 50+ year series for winter, autumn and the year. 81% of the annual and 72% of the winter series show positive trends (0–3% per decade) for the 1901–2013 period. The trends are significant for 34% (22%) of the annual (winter) series. Long‐term trends are generally in line with earlier estimates in literature considering somewhat shorter time periods. Significantly negative trends are only found for winter in the most recent decades. No significant trends are found for inter‐annual variability and changes in the 10th and 90th percentile seasonal extreme precipitation thresholds. The influence of large‐scale flow on precipitation variability is strongest in winter. The leading pattern for northern Switzerland (nS) is the Euro‐Atlantic blocking pattern. For southern Switzerland (sS), the Eastern Atlantic (Scandinavian) pattern is dominant in winter (autumn). In nS, wet (dry) seasons are linked to south‐westerly (north‐easterly) flow. In sS, wet (dry) seasons are linked to southerly (northerly) flow. Strong evidence for imprints of atmospheric blocking on seasonal precipitation variability is found in winter and autumn. In spring, a high pressure anomaly stretching from the mid‐Atlantic to central Europe is indicative of dryness in nS.